2022
DOI: 10.3389/fendo.2022.1018450
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of type 2 diabetes mellitus using the traditional Chinese medicine Jinlida as an add-on medication: A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundNumerous randomized controlled trials (RCTs) conducted in China have shown that jinlida granules are a promising traditional Chinese medicine (TCM) for the treatment of persons with type 2 diabetes mellitus (T2DM). Controversial results have been reported in different RCTs. The aim of our study was to evaluate the adjuvant hypoglycemic effect of jinlida granules on persons with T2DM and to explore the source of heterogeneity between these RCTs.Materials and methodsMedical article databases were indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…A systematic review and meta-analysis of randomized controlled trials (RCT) showed that Jinlida Granules statistically and clinically reduced fasting plasma glucose, 2 hours plasma glucose and HbA1c in patients with T2D [ 25 ]. Few recent systematic review and meta-analysis of another RCT showed that the addition of the TCM in the treatment of T2D has a statistically significant effect on reducing HbA1c in Chinese adult patients with T2D [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of randomized controlled trials (RCT) showed that Jinlida Granules statistically and clinically reduced fasting plasma glucose, 2 hours plasma glucose and HbA1c in patients with T2D [ 25 ]. Few recent systematic review and meta-analysis of another RCT showed that the addition of the TCM in the treatment of T2D has a statistically significant effect on reducing HbA1c in Chinese adult patients with T2D [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the current evidence of the trials, both Jinlida and metformin reduced the level of blood glucose, and the curative effect of Jinlida add-on metformin was superior to metformin monotherapy ( 10 13 ). In terms of the standard-reaching rate of blood glucose, Jinlida add-on metformin has obvious advantages in comparison to metformin monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that glycosylated hemoglobin (HbA1c) was reduced more significantly in the Jinlida group ( 10 , 11 ). Furthermore, meta-analysis and systematic reviews of Jinlida granules showed significant reductions in fasting blood glucose (FBG), 2-h postprandial blood glucose (2hPG), and HbA1c ( 12 , 13 ). Animal experiments show that Jinlida granules could promote the thermogenesis of brown and beige adipocytes by enhancing the mitochondrial function and inhibiting the expression of miR-27a, thereby improving the metabolism of glucose and lipids ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…TCPMs that have been reported to combine with anti-hyperglycemic drugs to treat T2DM include Jinlida granules, Yuquan pill, and Tianqi capsules, etc. One systematic review demonstrated that integrated Jinlida granule and metformin were found to significantly improve HbA1c in subjects exhibiting poor glucose control as compared to metformin alone (7). Another trial demonstrated that after 12 weeks of treatment Tianqi capsule combined with metformin decreased the level of HbA1c and blood lipid indicators, and promoted insulin secretion in T2DM as compared with metformin alone (8).…”
Section: Introductionmentioning
confidence: 99%